Reflecting on the Past, for the Sake of the Future - Erling, Maria E. (Dialog, 2010)
The Lutheran decision to ordain women happened in two broader contexts—ecumenical and inter-Lutheran—that still influence the way that the decision has been received in the congregations and in the wider public realm. Ordained women have not “arrived” yet, but the ongoing journey has been interesting and rewarding.